2022
DOI: 10.5603/mrj.a2022.0058
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on hospital functioning and mortality among non-COVID-19 patients

Abstract: Introduction:The pandemic resulted in significant changes in the work organization within medical facilities, mainly hospitals, which were handling the largest numbers of people infected with SARS-CoV-2. The objective of the study was to analyse the impact of the COVID-19 pandemic on the functioning of Antoni Jurasz University Hospital No. 1 in Bydgoszcz as a whole, as well as consider individual departments.Material and methods: The data were acquired from the database of Antoni Jurasz University Hospital No.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The COVID-19 pandemic has undoubtedly impacted the functioning and day-to-day patient care at medical facilities, including the Dr Antoni Jurasz University Hospital No. 1 in Bydgoszcz [6][7][8][9]. In the presented study analysing the group of 27,209 patients hospitalized at the aforementioned hospital between 2019 and 2021, it was found that those vaccinated were significantly less likely to test positive for COVID-19.…”
Section: Discussionmentioning
confidence: 58%
“…The COVID-19 pandemic has undoubtedly impacted the functioning and day-to-day patient care at medical facilities, including the Dr Antoni Jurasz University Hospital No. 1 in Bydgoszcz [6][7][8][9]. In the presented study analysing the group of 27,209 patients hospitalized at the aforementioned hospital between 2019 and 2021, it was found that those vaccinated were significantly less likely to test positive for COVID-19.…”
Section: Discussionmentioning
confidence: 58%
“…Overburdened healthcare systems have had an impact on out-of-hospital cardiac arrest (OHCA) [4,5]. There has been an increase in OHCA in recent years, which is believed to be linked to COVID-19-related illnesses, patients' difficulty getting preventive or general medical treatment, and their unwillingness to seek care due to the risk of COVID-19 transmission in hospitals [6,7]. The challenge arises from the potential transmission of the SARS-CoV-2 virus to first responders who are engaged in administering cardiopulmonary resuscitation (CPR), necessitating careful consideration of how to effectively handle CPR during the pandemic [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, the pandemic has impacted every aspect of our lives, including and especially the healthcare system [9][10][11][12][13][14][15]. It appears that this topic as well as the virus itself is here to stay.…”
mentioning
confidence: 99%